Neonatal leukemoid reaction due to early-onset neonatal sepsis in a premature infant. A case report - L.D. Anguiano Sánchez; L.P. Islas Domínguez (Revista Médica del Hospital General de México, 2015)
We describe an unusual case of leukemoid reaction secondary to congenital infection associated with prematurity as a finding in the study protocol. The haematological and clinical evolution of the newborn was satisfactory.